Monitoring exposure to polycyclic aromatic hydrocarbons in an Australian population using pooled urine samples - Thai, Phong K. (Environ Int, 2015)
Integrated exposure to polycyclic aromatic hydrocarbons (PAHs) can be assessed through monitoring of urinary mono-hydroxylated PAHs (OH-PAHs). The aim of this study was to provide the first assessment of exposure to PAHs in a large sample of the population in Queensland, Australia including exposure to infant (0–4 years). De-identified urine specimens, obtained from a pathology laboratory, were stratified by age and sex, and pooled (n = 24 pools of 100) and OH-PAHs were measured by gas chromatography-isotope dilution-tandem mass spectrometry. Geometric mean (GM) concentrations ranged from 30 ng/L (4-hydroxyphenanthrene) to 9221 ng/L (1-naphthol). GM of 1-hydroxypyrene, the most commonly used PAH exposure biomarker, was 142 ng/L. The concentrations of OH-PAHs found in this study are consistent with those in developed countries and lower than those in developing countries. We observed no association between sex and OH-PAH concentrations. However, we observed lower urinary concentrations of all OH-PAHs in samples from infants (0–4 years), children (5–14 years) and the elderly (>60 year old) compared with samples from other age groups (15–29, 30–44 and 45–59 years) which may be attributed to age-dependent behaviour-specific exposure sources.